Causes and Pathology of LeftHandedness - Gulbakhor Abdullayevna Gaynazarova (Genius Publishing Group, 2023)
If a child is left-handed, is it necessary to teach him to write and eat with his right hand, forcing him? By no means impossible. Otherwise, the qualities inherent in lefties, such as football, drawing and interest in music, which are now gaining momentum, will disappear. In addition, getting used to lefties and tens can make a child nervous and sluggish. So lefty is not a fault or a disease. Only the fact that all the equipment is designed for right-handed people can cause them a little discomfort. The article discusses the origin of left-handers, their types
Keywords: Lefty; right hemisphere; left hemisphere; ambidextrous